Provision of palliative care in National Cancer Grid treatment centres in India: a cross-sectional gap analysis survey. Issue Volume 12:Issue e3(2022) (9th June 2020) - Damani, Anuja; Salins, Naveen; Ghoshal, Arunangshu; Chowdhury, Jayeeta; Muckaden, Mary Ann; Deodhar, Jayita; Pramesh, CS
Abstract : Objectives: This study aimed to identify gaps in palliative care (PC) provision across the National Cancer Grid (NCG) centres in India. Methods: We performed a cross-sectional validated web-based survey on 102 NCG cancer centres (Nov '17 to April '18). The survey questionnaire had seven sections collecting data relating to the capacity to provide cancer care and PC, drug availability for pain and symptom control, education, advocacy, and quality assurance activities for PC. Results: Eighty-nine NCG centres responded for this study—72.5% of centres had doctors with generalist PC training, whereas 34.1% of centres had full-time PC physicians; 53.8% had nurses with 6 weeks of PC training; 68.1% of the centres have an outpatient PC and 66.3% have the facility to provide inpatient PC; 38.5% of centres offer home-based PC services; 44% of the centres make a hospice referral and 68.1% of the centres offer concurrent cancer therapy alongside PC. Among the centres, 84.3% have a licence to procure, store and dispense opioids, but only 77.5% have an uninterrupted supply of oral morphine for patients; 61.5% centres have no dedicated funds for PC, 23.1% centres have no support from hospital administration, staff shortage—69.2% have no social workers, 60.4% have no counsellors and 76.9% have no volunteers. Although end-of-life care is recognised, there is a lack of institutional policy. Very few centres take part in quality control measures. Conclusions: The majority of the NCG centres have the facilities to provide PC but suffer from poor implementation of existing policies, funding and human resources.